Por onde o mar passou: a relevância de se Musealizarin situ os Afloramentos Fossilíferos da praia do Atalaia, em Salinópolis - PA - OLIVEIRA JUNIOR, Emanoel Fernandes de (2019)
A major challenge for contemporary nations is to rethink models of economic and social development from their own realities, demand which effective participation of different actors is a major factor in its success. In this context, museums and cultural heritage are configured as supporters in the formation of a new political agency, since they are learning and interaction spaces between different audiences. From this premise, the present study aims to analyze how the fossil heritage at Atalaia Beach, city of Salinopolis, northeastern Pará, in the North region of Brazil, can assist in the development of the local community. Found in an area of intense tourism and urban expansion, such heritage is formed by outcrops of carbonate rocks belonging to the Pirabas Formation, geological unit that goes back 23 million years (Oligo-Miocene) and whose informational value is mentioned in the literature science since the late nineteenth century, but still unknown to the general public. Thus, the proposal of musealization in situ of this paleontological record is inserted both in the conservation of its documental capacity as the communication of its importance to the people around it, in order that this space may arise as an area of dialogue between university, with its peculiar vision of the heritage, and the population, which has different ways of appropriating it, so that a shared management of the site can be considered from their educational and economic potential.